ДИНАМИЧЕСКИЕ ХАРАКТЕРИСТИКИ ВЫПРЯМИТЕЛЯ С ШИРОТНО-ИМПУЛЬСНОЙ МОДУЛЯЦИЕЙ - Щербак , Я.В.; Ивакина , Е.Я. (Інститут електродинаміки НАН України, Київ, 2014)
The paper considers the dynamical properties rectifier with regulation the average value of the output voltage using a pulse width modulation. Dynamic characteristics investigated by allocating the information component the output coordinates at of infinitesimal increments of control action with further decomposition using the method of generalized differentiation in a Taylor series. The analytical dependences establishing the connection between the increment of input influence and output voltage is obtained. For infinitesimal increments of the input influence rectifier with pulsewidth modulated represents amplitude-width modulator of the second kind with variable values of the static and dynamic transmission coefficients is established. References 10, figures 3.